Synopsis of the conference on accelerating agricultural development, economic growth and poverty reduction in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The Ethiopian Strategy Support Program (ESSP-II) Conference on “Accelerating Agricultural Development, Economic Growth and Poverty Reduction in Ethiopia” was held at the Addis Ababa Hilton Hotel from October 22-24. This conference was organized to share current and ongoing research efforts of IFPRI – ESSP-II researchers and collaborating Ethiopian Institutions. Ato Newai Gebre-Ab (Chief Economic Advisor to the Prime Minister and Executive Director, EDRI) attended all three days of the conference, as did Wro. Samia (Director General of CSA) and other high level figures from a variety of government ministries.